Evaluation of Electric Field for a Dielectric Cylinder Placed in Fractional Space: Evaluation of Electric Field for a Dielectric Cylinder Placed in Fractional Space - Akbar, M.; Shahzad, M. Imran; Ahmed, Saeed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
The problem related to the dielectric cylinder placed in non-integer dimensional space (FD space) isthoroughly investigated in this paper. The FD space describes complex phenomena of physics and electromagnetism. We have solved Laplacian equation in FD space to obtain the solution of a dielectric cylinder in low frequency. The problem is solved by the method of separation of variables analytically. The classical solution of the problem can be easily recovered from the derived solution in non-integer dimensional space.